The evolution of symbiotic innovation, water, and agricultural supply chains - Zilberman, David; Huang, Alice; Goldberg, Lanie; Reardon, Thomas (Wiley, 2023)
The water literature has mainly investigated the diversion and distribution of water from the source to the end users or the utilization of water at the farm level in crop production. This paper presents a supply chain perspective that links the innovation supply chain of water delivery and irrigation with the complete water supply chain to the crop and the crop supply chains. These supply chains are symbiotic. Changes in the demand for crops, agronomic technology, and knowledge about water will modify the water infrastructure, irrigation technology, land-use and crop production patterns, and the pricing of water and related commodities. The parameters that guide investment in water innovation and the design of the water supply chain depend on political, economic, and technological considerations that have coevolved over time with water and crop systems. Evidence from California and elsewhere supports the findings of the paper.